Interaction of Cetylpyridinium Chloride and Methylene Blue in Methanol-Water Solvent Media - Shrestha, Lalita; Rai, Debendra; Subba, Prince; Bhattarai, Ajaya (Himalayan Journal of Science and Technology, 2018)
The interaction of Methylene blue with Cetylpyridinium chloride (CPC) in a series of solvents containing 0.1, 0.2 and 0.3 volume fractions of methanol in water were studied at room temp (300±2 K) by UV-Vis spectrophotometer. The CPC concentrations were varied from 0.2 x 10-3 to 2 x 10-3 mol dm-3. A fixed dye concentration of 2.5 x 10-5 mol dm-3 was used for this purpose. The spectrum analysis was performed for both the dye solution and mixtures containing dye and surfactant of different concentrations. The dye solution showed the absorbance maximum at 664 nm and a shoulder at 610 nm. In 0.3 volume fraction of methanol as solvent, the dye and surfactant mixed solution showed a shift in peak values towards shorter wavelength (blue shift) from peak of the dye solution. The shift in peak increased with increase in surfactant concentration up to 0.6 x10-3 mol dm-3, beyond which no further shift increment occurred. In the case of 0.1 and 0.2 volume fractions of methanol in water, no shift in peak was found at all concentrations of dye and surfactant. The absorbance of dye and surfactant mixed solution decreased gradually in 0.2 volume fraction of methanol with increase in surfactant concentration, whereas no significant change in absorbance was seen in 0.1 volume fraction of methanol. The shift decreased gradually with decrease in methanol concentration in the solvent.